2018
DOI: 10.1016/j.acap.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Familiarity With Developmental Disabilities Among Low-Income Parents

Abstract: Low-income Latino-LEP and other race parents have less familiarity or personal experience with DDs and are less aware of early signs of DDs compared to low-income white parents. Study findings suggest that interventions to reduce disparities in DD diagnosis and treatment should include increasing information transfer to parents in racial/ethnic and language minority communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…He said, ''A-u-t-i-s-m.'' In addition to explaining global differences in recognition of autism symptoms, culture and context may also contribute to within-country differences in autism awareness. A recent study in a low-income sample of families in the USA suggested that compared to white parents racial/ethnic minority parents and especially Latino parents had less familiarity or personal experience with people with developmental disabilities, and were less aware of early signs of developmental disabilities (Zuckerman, Chavez, Murillo, Lindly, & Reeder, 2018). Limited awareness about autism and low mental health literacy may be directly related to the availability, accessibility and acceptability of healthcare professionals, a topic discussed in more detail under level 4 of this framework.…”
Section: Literacy In Mental Health and The Typical Child Developmentamentioning
confidence: 99%
“…He said, ''A-u-t-i-s-m.'' In addition to explaining global differences in recognition of autism symptoms, culture and context may also contribute to within-country differences in autism awareness. A recent study in a low-income sample of families in the USA suggested that compared to white parents racial/ethnic minority parents and especially Latino parents had less familiarity or personal experience with people with developmental disabilities, and were less aware of early signs of developmental disabilities (Zuckerman, Chavez, Murillo, Lindly, & Reeder, 2018). Limited awareness about autism and low mental health literacy may be directly related to the availability, accessibility and acceptability of healthcare professionals, a topic discussed in more detail under level 4 of this framework.…”
Section: Literacy In Mental Health and The Typical Child Developmentamentioning
confidence: 99%
“…The importance of understanding provider perceptions of the benefits and barriers to ASD tele-assessment extends beyond the immediate and relatively short-term impacts of COVID-19. Delays in accessing ASD-specific diagnostic and intervention services, specifically for underserved and under-resourced populations, were present long before the pandemic (Constantino et al, 2020a, b;Durkin et al, 2017;Wallis et al, 2020;Zuckerman et al, 2017Zuckerman et al, , 2018 and will undoubtedly continue after its cessation without significant, systemic intervention. Telemedicine has the potential for increasing access to care for those families who might otherwise face delays.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In addition to explaining global differences in recognition of autism symptoms, culture and context may also contribute to within-country differences in autism awareness. A recent study in a low-income sample of families in the USA suggested that compared to white parents racial/ethnic minority parents and especially Latino parents had less familiarity or personal experience with people with developmental disabilities, and were less aware of early signs of developmental disabilities (Zuckerman, Chavez, Murillo, Lindly, & Reeder, 2018). Limited awareness about autism and low mental health literacy may be directly related to the availability, accessibility and acceptability of healthcare professionals, a topic discussed in more detail under level 4 of this framework.…”
Section: Literacy In Mental Health and The Typical Child Developmentamentioning
confidence: 99%